Tren Perkembangan Penelitian tentang Literasi Informasi pada Penelitian Mahasiswa Ilmu Perpustakaan dan Informasi Universitas Padjadjaran - Andri Yanto; Wina Erwina (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2017)
The study of information literacy among students of Library and Information Science that exists throughout the University in Indonesia showed an increase. This is apparent in the researches of students in graduation thesis which has been created by graduates of undergraduate or master's degree in Library and Information Science in Indonesia. This happens also among students of Library and Information Science Fikom and served with improved information literacy study conducted the students to complete a final project. This study aims to find out the trend of the development of the research on information literacy in the thesis students of Library and Information Science Padjadjaran University. Methods in this study is a library research. Results of the study showed total use of literacy or information literacy concepts on student research conducted as many as 22 titles and there are 15 thesis/theses (68.2%) who use the models of information literacy to address a variety of problems that they are scrupulous or become a source of reference for determining the various concepts for the benefit of their research. Big 6 model widely used student. The following models used information literacy: Big 6; Information Literacy model 7 steps of Knowledge Management; The Seven Pillars Of Information Literacy SCONUL; Empowering 8; Model 6-Scientific Information Literacy Model; Plus Model; Pattern and Model LISA; ACRL Literacy Model (Information Literacy Competency Standards For Higher Education).